Pontine haemorrhage mimicked by an olanzapine overdose. Issue 4 (20th March 2006) - Broyd, C; McGuinness, A
Abstract : Olanzapine, an atypical antipsychotic of the thienobenzodiazepine class, has been on the market since 1996. Its popularity has increased over recent years because of excellent clinical results as well as a favourable side effect profile. Mirroring this increased olanzapine use has been a rise in the number of non-accidental overdoses. The clinical picture of olanzapine overdose can be surprisingly variable. In the case presented, the patient's low Glasgow Coma Score prevented an accurate history being taken. Examination revealed bilateral upgoing plantars, pinpoint pupils, increased tone, and brisk reflexes; however initial investigations, including an urgent CT head, were normal. The patient required 24 hours of intensive care before he regained consciousness and admitted to the overdose. Although there are several reports of olanzapine mimicking opiate intoxication in overdose, this is one of the first cases where overdose has mimicked an intracerebral event. The authors highlight some of the literature regarding clinical presentation and treatment options, and discuss the relation between olanzapine therapy and diabetes.